FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA AUDITOR DENGAN INDEPENDENSI AUDITOR DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Handayani, Dwi (Widya Warta, 2017)
The research purpose was to obtain empirical evidences on the factors influencing the auditor performance with the auditor independence and the organizational commitment as the intervening variables. The research population was auditors working in the firm of auditors in central java. The samples were 28 auditors. The results showed that the understanding of good governance did not affect the performance of auditors but affected the independence of auditors. The leadership style did not affect the auditor performance or the organizational commitment. The organizational culture did not affect the auditor performance or the organizational commitment. The independence affected the performance of auditors. The organizational commitment affected the auditor performance. The understanding of good governance having an indirect effect on auditor performance through auditor independence was proven. The leadership style having an indirect effect on auditor performance through organizational commitment was not proven. The organizational culture having an indirect effect on auditor performance through organizational commitment was not proven.